Occupational Injury Among Janitors: Injury Incidence, Severity, and Associated Risk Factors. Issue 2 (February 2019) - Green, Deirdre R.; Gerberich, Susan G.; Kim, Hyun; Ryan, Andrew D.; McGovern, Patricia M.; Church, Timothy R.; Schwartz, Adam; Arauz, Rony F.
Abstract : Objective: Determine injury incidence and severity and potential associated risk factors for injury, among janitors. Methods: Questionnaires were disseminated to 1200 full-time janitors in the Service Employees International Union (SEIU) Local 26 union; 390 responded and provided information on their injury experiences and exposures, based on personal characteristics and work-related activities. Multivariable analyses, including bias adjustment, were implemented using directed acyclic graphs to determine potential risk. Results: Among the janitors, 34% reported experiencing at least one injury; 16% of cases resulted in hospital admittance. Significantly increased risks were identified for age, ethnicity, shift start time, and physician-diagnosed depression. Conclusions: Knowledge of specific risk and protective factors is valuable, and can serve as a basis for further in-depth studies and inform the development of targeted intervention strategies aimed to reduce occurrence of these injuries.